Kewenangan Kurator Dalam Mengeksekusi Aset Debitor Pada Kepailitan Lintas Batas (Cross Border Insolvency) - Okta Putri Setia Ningtias (Al Qodiri : Jurnal Pendidikan, Sosial dan Keagamaan, 2024)
Article 1 of Law No. 37/2004 on Bankruptcy and Postponement of Debt Payment Obligations, what is meant by Bankruptcy is a general confiscation of all assets of the Bankrupt Debtor whose management and management is carried out by the Curator under the supervision of the Supervisory Judge as regulated in this Law. Guidelines for the execution of the assets of Bankrupt Debtors located outside Indonesia are not regulated in Law Number 37 Year 2004 on Bankruptcy and Suspension of Debt Payment Obligations. Furthermore, Indonesia is not bound by an international agreement related to cross-border insolvency, so that bankruptcy decisions rendered by the Indonesian Commercial Court do not have executorial power outside Indonesia. Therefore, this will lead to the inability to sell the assets of the Bankrupt Debtor to be used as payment to its Creditors. This research uses the juridical-normative method by examining bankruptcy legislation. This research shows that there are no legal provisions that result in legal uncertainty. And the need to regulate the law related to the authority of the curator in executing the debtor's assets in cross-border bankruptcy. Keywords: Curator; Debtor Assets; Cross-border.